2001
DOI: 10.1002/jrs.728
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational analysis of Ni(II)‐ and Cu(II)‐octamethylchlorin by polarized resonance Raman and Fourier transform infrared spectroscopy

Abstract: We measured the polarized resonance Raman spectra of Cu(II)-2,2,7,8,12,13,17,18-octamethylchlorin in CS 2 at various excitation wavenumbers in a spectral region covering the Q y , Q x and B x optical absorption bands. Additionally, we measured the FTIR-Raman spectrum of the highly overcrowded spectral region between 1300 and 1450 cm −1 . The spectral decomposition was carried out by a self-consistent global fit to all spectra obtained. The thus identified Raman and IR lines were assigned by comparison with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Generally, values of the unmixing factor lie between 0.05 and 0.15 [50][51][52]. The situation changes dramatically when the symmetry of the heme chromophore is substantially perturbed as it is the case in hydroporphyrins like metallochlorins and chlorophylls [53,54]. In this case, the original MO-transitions are no longer accidentally degenerate and as a consequence the unmixing factor becomes very large.…”
Section: Optical Spectra Of Metalpor-phyrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, values of the unmixing factor lie between 0.05 and 0.15 [50][51][52]. The situation changes dramatically when the symmetry of the heme chromophore is substantially perturbed as it is the case in hydroporphyrins like metallochlorins and chlorophylls [53,54]. In this case, the original MO-transitions are no longer accidentally degenerate and as a consequence the unmixing factor becomes very large.…”
Section: Optical Spectra Of Metalpor-phyrinsmentioning
confidence: 99%
“…The total set of macrocycle modes contains of course more than one representative for each symmetry, which seem to suggest that it might be difficult to unambiguously decompose an observed heme deformation into individual contributions from a set 21 oop-and 45 ip-normal coordinates. These numbers would even increase for porphyrins with bulky substituents, since macrocycle and substituent modes generally mix [54,106]. However, the situation is simpler owing to the fact that the energy, which has to be invested for distorting the heme along a distinct coordinate, is proportional to the square of the frequency of the respective normal mode [79,104].…”
Section: Experimental Investigations Of Heme Deformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…by an excited state displacement along the normal coordinate of the vibration with respect to the respective equilibrium position in the deformed ground state. 39,43,44 When the heme is perturbed into a lowered symmetry, substituent modes and macrocycle modes of the same symmetry vibrationally mix, especially when their vibrational frequencies are in close proximity. 39 Raman bands from oop deformations such as doming (A 2u ), ruffling (B 1u ) and waving (E g ) have been identified in the low-wavenumber region of the Raman spectra, as well as some bands of ip modes and of substituents, deformations, (ruffling), 21 and 22 (waving), which correspond to the dominant SNCDs found for the heme groups of the three investigated cytochrome c molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Egawa et al also reported that the A 2 modes should be considered as the best means for elucidating the vibronic character of the absorption bands of porphyrins. [15,34] B y -band THPP photodissociation dynamics and comparison with previous work on porphyrin…”
Section: Rr Depolarization Ratiosmentioning
confidence: 99%